Digital Reporting System for Product Quality Using Normal Distribution and EWMA Control Chart - Dwipa Handayani; Andy Achmad Hendharsetiawan; Muhammad Yasir (LPPM Universitas Islam 45 Bekasi, 2025)
The collection and reporting of product quality at CV. Sinar Agung Teknik is still done manually, which is time-consuming, inefficient, and prone to errors. This study aims to digitize the reporting process to improve efficiency, accuracy, and speed up information distribution between departments. The system developed uses a normal distribution algorithm in product quality data analysis because it is in line with the characteristics of quantitative data that is distributed close to normal. The research stages include needs identification, form digitization, statistical analysis integration, and employee training. The results of the implementation show that the product quality reporting digitization system is capable of improving the accuracy of analysis, speeding up reporting, reducing human error, and increasing operational efficiency, with positive feedback from users regarding its ease of use and benefits in quality data management.